My unforgotten Seattle - Chew, Ron (International Examiner Press, 2020)
"My Unforgotten Seattle is a deeply personal collection of vignettes by journalist and community organizer Ron Chew. The author narrates his life journey with a rich cast of characters set against a backdrop of chop suey restaurants and sewing factories in a small town growing too fast to preserve its soul. In powerful simple strokes, Chew tells of his awkward years as the child of Chinese immigrants and the discovery of his family's hidden past. He retraces the political awakening that led to his celebrated career as editor of an Asian American community newspaper and national museum authority. This book is a revealing tapestry of ordinary stories made extraordinary by the author's dexterity at capturing everyday moments for us to treasure." --Back cover.